Phosphomolybdic Acid-Fe₃O₄ Modified Sludge-Biochar with Tetracycline Adsorption Properties - Fanaei, Giang; Piekacz, Marwa; Meath, Loan (Journal of Functional Materials and Applied Engineering, 2026)
To address the pressing issue of antibiotic contamination in wastewater, this study developed a novel phosphomolybdic acid (PMA)-Fe₃O₄ ball-milled co-modified sludge-based biochar (PFBC) for tetracycline (TC) removal. Using waste-activated sludge as a precursor, the PFBC composite was synthesized via low-temperature pyrolysis followed by sequential PMA functionalization and mechanochemical Fe₃O₄ incorporation. Comprehensive characterization confirmed that this co-modification strategy successfully enhanced the material's specific surface area, pore volume, and the concentration of surface oxygen-containing functional groups while incorporating magnetic nanoparticles. Batch adsorption tests demonstrated that PFBC exhibited excellent TC sequestration performance, achieving 88.7% removal under optimal conditions (30 mg/L TC, 0.25 g/L PFBC, pH 7). The adsorption followed the Langmuir isotherm and pseudo-second-order kinetic models, with a maximum theoretical capacity of 500.0 mg/g at 25°C. Furthermore, PFBC showed good practical utility with easy magnetic separation (saturation magnetization: 18.1 emu/g) and maintained over 63.3% removal efficiency after five adsorption-desorption cycles.